ONLINE BUYING AND SELLING TRANSACTIONS UNDER INTERNATIONAL PRIVATE LAW - Lubis, Muhammad Ikhsan (JOURNAL OF PRIVATE AND COMMERCIAL LAW, 2018)
Development of business transactions especially buying and selling has globally impact to daily activities, and in modern era it disrupted by technology. Distance and time was no longer an obstacle in terms of getting the desired goods or services. The buying and selling transaction is then called online buying and selling transaction, a term commonly used by business actors in Indonesia and even the world. Civilizations and actions of a person change drastically in fulfilling his desire to get something what he wants. The online buying and selling transaction is even considered the 5th Industrial Revolution for the order of trade and industrial civilization in the world today. This paper will see and examine online buying and selling transactions from the perspective of the International Private Law, because it is not impossible this online buying and selling transactions cross the border of the country. It is hoped that this paper will give different insight and perspective for readers about online transaction.